Potential‐Dependent Adlayer Structure and Dynamics at the Ionic Liquid/Au(111) Interface: A Molecular‐Scale In Situ Video‐STM Study1. Issue 20 (27th April 2015) - Wen, Rui; Rahn, Björn; Magnussen, Olaf M.
Abstract Room‐temperature ionic liquids are of great current interest for electrochemical applications in material and energy science. Essential for understanding the electrochemical reactivity of these systems are detailed data on the structure and dynamics of the interfaces between these compounds and metal electrodes, which distinctly differ from those in traditional electrolytes. In situ studies are presented of Au(111) electrodes in 1‐butyl‐1‐methylpyrrolidinium bis(trifluoromethylsulfonyl)imide ([BMP][TFSA]) by high‐speed scanning tunneling microscopy (video‐STM). [BMP][TFSA] is one of the best‐understood air and water stable ionic liquids. The measurements provide direct insights into the potential‐dependent molecular arrangement and surface dynamics of adsorbed [BMP]+ cations in the innermost layer on the negatively charged Au electrode surface. In particular, two distinct subsequent transitions in the adlayer structure and lateral mobility are observed with decreasing potential.